Social Cash Transfer in Turkey Toward Market Citizenship - Ark-Yıldırım, Ceren; Smyrl, Marc (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access book asks whether cash-transfer programs for very low-income households promote social and economic citizenship and, if so, under what conditions. To this end, it brings together elements that are too often considered separately: the transformation of social and economic citizenship rights in a market-centered context, and the increasing popularity of cash transfer as an instrument both of social policy and humanitarian action. We link these by juxtaposing theoretical treatment of citizenship and inclusion with concrete policy case studies set in contemporary Turkey. Cases are taken both from domestic social policy and international relief efforts aimed at Syrian refugees. Theoretical discussion and case studies lead to the conclusion that cash transfer programs can promote economic and social inclusion - if deployed at an appropriate scale; if sufficient financial, technical, and social resources are available; and if program design and implementation promotes market inclusion of beneficiaries both as consumers and workers. Ceren Ark-Yıldırım is Assistant Professor in the department of Political Science and Public Administration of Istanbul University, Turkey. Her research focuses on migration, cash transfer programs, and urban governance, and has appeared in journals such as Turkish Studies and South European Policy and Politics. Marc Smyrl is Associate Professor in the department of Political Science at the University of Montpellier, France, where he directs the MA program in International Cooperation and Development. His research on comparative social policy has appeared in journals such as Governance and the Journal of Health Politics Policy and Law. .